Nuances of Arteriovenous Fistula Creation for Vascular Access in Hemodialysis - Parag Sahasrabudhe; Ameya Bindu (Indian Journal of Plastic Surgery)
Background With rising incidence and increased life expectancy of patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD), the number of patients requiring hemodialysis has increased substantially. Vascular access is the lifeline for a patient on hemodialysis (HD), and an arteriovenous fistula (AVF) is the undisputed gold standard for HD access. An effective and long-lasting fistula serves to increase the life expectancy of ESRD patients and improves their quality of life. Learning Objectives This paper aims to give a comprehensive overview of AVF creation, including the various techniques, patient selection, troubleshooting with decision-making, and common complications. Authors share their experience from previous publications and over 2000 AVF surgeries. They have not only described a new modification of the technique of proximal fistula but have also established a direct correlation between bruit and thrill on operation table and success of fistula surgery. Conclusion A standardized, protocol-driven multidisciplinary approach with careful patient and site selection, guided by outcome predictors, is vital in AVF surgery. Knowledge about the potential complications of AVFs contributes to their timely detection and allows measures to be taken that might prevent deleterious consequences that range from loss of vascular access to serious morbidity and mortality.